Female oxidative status in relation to calcium availability, metal pollution and offspring development in a wild passerine - Espín S; Sánchez-Virosta P; Ruiz S; Eeva T (ELSEVIER SCI LTD, 2025)
Both Ca deficiency and metal exposure may affect physiological and nutritional condition of breeding females altering their ability to deposit essential resources (e.g. Ca, antioxidants) into the eggs. This effect of the maternal investment into egg quality is not strictly limited to the embryonic period, but may persist after hatching, since nutrient levels in yolks can compromise nestling antioxidant status, growth and fledging success. The goal of this study was to investigate how metal pollution and Ca availability during the breeding season affect oxidative stress biomarkers and plasma biochemistry in adult female pied flycatchers (Ficedula hypoleuca). In addition, we aim to evaluate how maternal antioxidant status and body condition relate to breeding parameters and offspring oxidative balance. Females breeding in a metal-polluted area in SW Finland showed higher metal concentrations compared to the control area, although current levels were below the toxic level able to affect female physiology. In addition, Ca availability was not constraining female oxidative status and general health in the study area. Interestingly, our results suggested that antioxidant response to metals was better when Ca concentrations were high enough to cover the physiological Ca requirements in breeding females. There seems to be a subtle balance between the concentrations of Ca in the organism and the tolerance to metal-related effects that requires further research. This study supports that offspring oxidative balance and nestling development are affected by maternal body condition and antioxidant status. (C) 2020 Elsevier Ltd. All rights reserved.